2011
DOI: 10.1530/erc-11-0155
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and Mek inhibition is synergistic in medullary thyroid carcinoma in vitro

Abstract: Clinical trials using kinase inhibitors have demonstrated transient partial responses and disease control in patients with progressive medullary thyroid cancer (MTC). The goal of this study was to identify potential combinatorial strategies to improve on these results using sorafenib, a multikinase inhibitor with activity in MTC, as a base compound to explore signaling that might predict synergystic interactions. Two human MTC cell lines, TT and MZ-CRC-1, which harbor endogenous C634W or M918T RET mutations, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…ERK is downstream of both the lapatinib and sorafenib targets, which may explain why MEK/ERK signaling was so critical to drug response in our data. In agreement with our findings, myeloid leukemia cells have a stiffness-dependent response to drugs, including sorafenib and a MEK inhibitor, which target the RAF/MAPK pathway 48, 49 . We have previously shown that sorafenib resistance increased with increasing hydrogel stiffness 10 , and many others have also demonstrated that stiffness is a significant driving force for drug resistance 9, 10, 30, 31, 50–53 .…”
Section: Discussionsupporting
confidence: 92%
“…ERK is downstream of both the lapatinib and sorafenib targets, which may explain why MEK/ERK signaling was so critical to drug response in our data. In agreement with our findings, myeloid leukemia cells have a stiffness-dependent response to drugs, including sorafenib and a MEK inhibitor, which target the RAF/MAPK pathway 48, 49 . We have previously shown that sorafenib resistance increased with increasing hydrogel stiffness 10 , and many others have also demonstrated that stiffness is a significant driving force for drug resistance 9, 10, 30, 31, 50–53 .…”
Section: Discussionsupporting
confidence: 92%
“…Overall, single agent MEK inhibitors have been limited as a front-line targeted therapy due to compensatory activation of other oncogenic signaling pathways (42, 47-50). This has necessitated an approach whereby MEK inhibitors are being tested in combination with other agents (51-56). Amongst the most common partners for MEK therapy are inhibitors of the PI3K/Akt pathway (50, 57-59).…”
Section: Discussionmentioning
confidence: 99%
“…This led the authors to test whether its effects could be enhanced by concomitant treatment with a MEK inhibitor. Indeed, combination with selumetinib (AZD6244, AstraZeneca) greatly increased growth inhibition compared to either single agent (Koh et al 2012). While this combination has not yet been further investigated in thyroid cancer, the addition of MEK/ERK inhibitors to upstream kinase inhibitors (e.g., BRAF) has proven very successful in other tumors (Robert et al 2015).…”
Section: Combination Therapiesmentioning
confidence: 99%